Prognosis and related risk factors analysis of total anomalous pulmonary venous connection correction. Issue 9 (2nd June 2022) - Wang, Zhangwei; Ding, Nan; Yi, Hanlu; Zhu, Yaobin; Li, Zhiqiang; Yan, Daole; Li, Xiaofeng; Bai, Song
Abstract: Objective: This study was performed to analyze the surgical outcomes of our center biventricular correction with total anomalous pulmonary venous connection (TAPVC) and to explore the risk factors associated with postoperative mortality and postoperative pulmonary venous obstruction (PVO). Methods: In total, 104 patients diagnosed with TAPVC and underwent biventricular correction from January 1, 2009 to December 31, 2021, in Beijing Children's Hospital Affiliated with Capital Medical University were included. The primary endpoints were early and late postoperative mortality and postoperative pulmonary vein obstruction. Results: Multivariable analysis indicated that prolonged cardiopulmonary bypass (CPB) time was the only independent risk factor for early postoperative mortality. Emergency surgery, preoperative moderate, and severe pulmonary hypertension (PH), and prolonged CPB time were independent risk factors for postoperative PVO. According to ROC curve analysis, the cut‐off value of CPB time for predicting early mortality was 148 min (AUC = 0.916, 95% CI 0.811–1.000). Conclusion: In the past 12 years, with surgical technique and perioperative management advancement, the prognosis of children treated with TAPVC biventricular correction in our center has generally improved. However, surgical repair remains challenging, and early mortality remains high in children with prolonged CPB time during surgery. Postoperative PVO often occurs in children who underwent emergency surgery, combined with moderate and severe PH and prolonged CPB time.